Attitude of rabies among dog bite victims in Srinagar, Kashmir - Namera Thahaby; Afzal Hoque Akand; Shabeer Ahmed Hamdani; Abdul Hai Bhat; Sanobar Rasool; Niha Ayman; Shiekh Shubeena (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2021)
Background: The Indian Association for the prevention and control of rabies estimates that 80, 00, 000 individuals receive the treatment for dog bites each year. The matter with dog rabies in India is that dogs are asymptomatic in each human establishment. The dog population is calculable to be about 25 million; most of them are ownerless and non-vaccinated against rabies. The purpose of the study was to see the attitude of dog bite victims towards rabies. Methods: The present study was carried in Srinagar district. Regarding the attitude of people, an interview schedule was formulated.  Results: With regards to all dogs are dangerous the majority, 82.50% agreed. When asked about stray dogs are vicious the majority, 82.50% agreed. Only 17.50% agreed that dogs bark when they are frightened. About attack for no reason, the majority 92.50% agreed. About roaming of stray dogs unless they cause problems in human society, just 17.50% agreed. The majority 92.50% didn't agreed about the person provoking the dog for an attack. Whilst 100% highlighted that stray dogs are a problem in Kashmir. When asked about the population of stray dogs 100% agreed that there are too many dogs in Srinagar. Conclusion: The attitude of the victimized people was positive. The majority, of respondents, alleged that stray dogs are a community vigour hitch within Srinagar. The outlook of respondents about not allotting stray dogs to meander copiously, appearing for medicinal consideration if bitten by a dog is shimmering proletariats concern in the control of rabies.